Determinants Of Organisational Effectiveness Among The Employees Of Automobile Industry In Tamilnadu (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The increasing dynamics in business landscape, such as changing market demands, diminishing product or service lifecycle and technological complexities, makes creating and sustaining competitive advantage a difficult feat for most organisations. The importance of innovation in paving way for business growth has been discussed in many literatures, including governmental reports and industrial white papers. Such an importance stems from the definition of innovation itself which is defined as the use of different resources in a combinative manner to seek differentiation in a competitive market (Dodgson et al., 2006). A similar trait exists in the automotive industry.This study proposed knowledge sharing as a potential mediator for the relationship between organizational factors (organizational climate, structure and leadership) and organizational effectiveness. This study also proposed ICT as a potential moderator for the relationship between organizational factors and knowledge sharing.Major findings of the study are: Most of 359 employees out of 400 forming 89.75 percentage are completed diploma. Employees with diploma qualification are interested to work in automobile industry. They have some awareness about the recent industrial policies which help them most. Majority of 384 employees out of 400 comprising 96 percentage has experience between 6 years to 10 years. Young generation employees have experience of 6 to 10 years. Eight components had extracted for the measuring the determinants of organisational effectiveness in automobile industry with reference to Tamilnadu with the overall influence of 81.59%. It has observed that the Knowledge sharing has the highest level of control based on the eigenvalue is 23.41%, Organizational climate has 19.78% of the variance, stress level has the influence of 10.50%, Organizational structure has 10.42% of control, Organizational leadership has 7.34% of control, Information and communication technology has 4.56% of control, strategies to overcome work life conflict has 2.94% of control and Organisational support has 2.65% of control.Major suggestions are: Based on the discussion with the employees, it is reveals that the level of dissemination of information is found to be low in the automobile industry. Hence, automobile industries need to understand the requirements of the employees and properly need to communication the information to the employees for enhancing their towards building the sustainable model for the effectiveness of the organisations. Strategies to overcome work life conflicts are found to be low to determine the effectiveness of the organisation. Hence, the organisation need to formulate strategies to overcome work life conflicts among the employees and formulate the quality councils. It is suggested that to spend money for impacting training to employees are the intellectual investments. Hence they must train their employees to acquire the latest training to improve their performance. It will be solution to reduce anxiety of new technologies. Employees are suggested that to acquire the knowledge towards latest technology. Thereby their level of stress regarding the performance of the organisation may reduced. Hence, if these findings and suggestions are to be taken in right direction, will bring more effectiveness in the organisation